1969
DOI: 10.1017/s0003356100026945
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the shape of the lactation curve in cattle

Abstract: SUMMARYThe lactation curve in cattle has been explained by the expression yn = Anbe-cn where yn is the average daily yield in the nth week, and A, b, and c are constants. In general, in a sample of 859 Friesian lactations recorded during 1964–65 daily yield was depressed during the winter months (18·8% in January) and stimulated during the spring (14·7% in May) to an extent which was independent of the stage of lactation. Winter calvers on the other hand tended to produce more in total lactation than spring ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
76
1
11

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(95 citation statements)
references
References 6 publications
7
76
1
11
Order By: Relevance
“…As a result, although only morning milk yield which is higher than evening milk yields (Quist et al, 2008) was evaluated, the estimated shape of lactation curves during the first 20 weeks of lactation were consistent with those reported by numerous previous studies (e.g. Wood, 1969;Walsh et al, 2007). Decline of milk protein and milk fat concen- tration during the first two months after parturition followed by a respective increase of values is in agreement with findings of Friggens et al (2007).…”
Section: Milk Yield and Milk Compositionsupporting
confidence: 89%
“…As a result, although only morning milk yield which is higher than evening milk yields (Quist et al, 2008) was evaluated, the estimated shape of lactation curves during the first 20 weeks of lactation were consistent with those reported by numerous previous studies (e.g. Wood, 1969;Walsh et al, 2007). Decline of milk protein and milk fat concen- tration during the first two months after parturition followed by a respective increase of values is in agreement with findings of Friggens et al (2007).…”
Section: Milk Yield and Milk Compositionsupporting
confidence: 89%
“…As reported by many authors (Wood, 1969;Danell, 1982;Wilmink, 1987b;Pé rochon et al, 1996), this study showed that daily yield was strongly affected by environmental factors such as region, year, parity, month of calving, age at calving, length of dry period before calving and pregnancy. In the 1980s, the objectives of most studies were to develop additive or multiplicative adjustment factors for lactation yield.…”
Section: Discussionsupporting
confidence: 73%
“…Calving month effect Many authors mentioned calving month as an effect with considerable influence on the cow's milk production (Wood, 1969;Danell, 1982;Wilmink, 1987b;Ptak et al, 1993). In this study, the effect of calving month was found to be significant on daily milk yield (Table 3).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Diversos estudos têm sido feitos em bovinos (WOOD, 1967(WOOD, , 1969(WOOD, , 1974, utilizando equações que possibilitem representar a curva de lactação com precisão.…”
Section: Introductionunclassified